Effects of stocking density on growth performance and production of Mola, Amblypharyngodon mola - M., Asadujjaman; M.A., Wahab; M.K., Fatema; Hossain, M. Belal; A.K.M.S., Azam (Universiti Kebangsaan Malaysia, 2013)
An experiment was conducted to determine the effects of stocking density on growth performance and production of Amblypharyngodon mola during 09 July to 09 October, 2011. There were three treatments, each with three replications in nine earthen ponds with an average depth of 1.5 m. Ponds of three treatments T1, T2 and T3 were stocked with mola at the density of 145000; 73000 and 36500 ind. ha-1. The water temperature, transparency, total alkalinity, pH, dissolved oxygen, nitrate-nitrogen, nitrite-nitrogen, ammonia-nitrogen, phosphate-phosphorus and chlorophyll-a of the ponds water were measured weekly. Among the water quality parameters, significant differences (p<0.05) were observed in case of temperature and dissolved oxygen. The lowest PO4-P and chlorophyll-a concentration were observed in T1. All water quality parameters were in suitable range of fish culture. The number of fishes at harvest were 15633.31±11.5; 84200±4 and 45600±7.21 indi. ha-1 in T1, T2 and T3, respectively. The mean weight of mola during harvest decreased significantly (p<0.05) with increasing stocking density. The net production of mola was significantly higher in treatment T3 (43.22±8.66 kg ha-1) than T2 (34.82±6.53 kg ha-1) and T1 (32.74±6.53 kg ha-1). Considering the highest net production among the three tested densities, the stocking density applied in T3 was found the best.